Performance globali e interculturali (tradotto e introdotto da Carmela Cutugno) - Richard Schechner (Mantichora, 2020)
The following essay is a section of the eighth chapter of “Performance Studies An Introduction” by Richard Schechner. The author, one of the fathers and leaders of the American Performance Studies, focuses on the analysis of what he defines as “Global and Intercultural Performances”. In the second part of his writing, starting from the assumption that “anything can be studied ‘as’ performance”, Schechner makes the ‘performative’ example of the jihad/terrorism, in order to understand how terrorism works, how it functions in a globalized world, and why its effects are far in excess of its actual death or property toll.